Development of NIRS calibration curves for sugars in baked sweetpotato - Amankwaah, Victor A.; Williamson, Sharon; Reynolds, Rong; Ibrahem, Ragy; Pecota, Kenneth V.; Zhang, Xiaofei; Olukolu, Bode A.; Truong, Van‐Den; Carey, Edward; Zum Felde, Thomas; Ssali, Reuben; Yencho, George Craig (Wiley, 2024)
Variability in sugar content between raw and cooked sweetpotato storage roots impact nutritional and dietary importance with implications for consumer preference. High-throughput phenotyping is required to breed varieties that satisfy consumer preferences.Near-infrared reflectance spectroscopy (NIRS) calibration curves were developed for analyzing sugars in baked storage roots using 147 genotypes from a population segregating for sugar content and other traits. The NIRS prediction curves had high coefficients of determination in calibration (R2c ) of 0.96 (glucose), 0.93 (fructose), 0.96 (sucrose), and 0.96 (maltose). The corresponding coefficients of determination for cross validation (R2cv ) were 0.92 (glucose), 0.89 (fructose), 0.96 (sucrose) and 0.93 (maltose) and were similar to the R2c for all sugars measured. The ratios of the standard deviation of the reference set to the standard error of cross validation were greater than three for all sugars. These results confirm the applicability of the NIRS curves in efficiently determining sugar content in baked sweetpotatoes storage roots. External validation was performed on an additional 70 genotypes. Coefficients of determination (r2 ) were 0.88 (glucose), 0.88 (fructose), 0.86 (sucrose) and 0.49 (maltose). The results were comparable to those found for the calibration and cross validation in fructose, glucose, and sucrose, but were moderate for maltose due to the low variability of maltose content in the population.NIRS can be used for screening sugar content in baked sweetpotato storage roots in breeding programs and can be used to assist with the development of improved sweetpotato varieties that better meet consumer preferences. This article is protected by copyright. All rights reserved.